2010
DOI: 10.1124/mol.110.064451
|View full text |Cite
|
Sign up to set email alerts
|

Methyl 2-Cyano-3,12-dioxooleana-1,9-dien-28-oate Decreases Specificity Protein Transcription Factors and Inhibits Pancreatic Tumor Growth: Role of MicroRNA-27a

Abstract: The anticancer agent 2-cyano-3,12-dioxooleana-1,9-dien-28-oic acid (CDDO) and its methyl ester (CDDO-Me) typically induce a broad spectrum of growth-inhibitory, proapoptotic, and antiangiogenic responses. Treatment of Panc1, Panc28, and L3.6pL pancreatic cancer cells with low micromolar concentrations of CDDO or CDDO-Me resulted in growth inhibition, induction of apoptosis, and down-regulation of cyclin D1, survivin, vascular endothelial growth factor (VEGF), and its receptor (VEGFR2). RNA interference studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
174
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 90 publications
(210 citation statements)
references
References 36 publications
35
174
1
Order By: Relevance
“…We recently reported that many of the responses/ genes affected by PEITC in pancreatic cancer cells were due to induction of ROS and ROS-dependent down-regulation of Sp1, Sp3, Sp4, and pro-oncogenic Sp-regulated genes (30). These results complement studies showing that hydrogen peroxide and t-butylhydroperoxide also down-regulate Sp proteins (22,23,27).BITC is structurally related to PEITC, and both compounds exhibit comparable anticancer activities and modulate expression of some common genes/pathways consistent with their effects on cancer cells (6 -14). It was also reported that BITC inhibits signal transducer and activator of transcription 3 (STAT3) phosphorylation and down-regulates STAT3 protein (6), and another study by the same group showed that BITC also induces ROS in pancreatic and other cancer cell lines (31-33).…”
supporting
confidence: 75%
“…We recently reported that many of the responses/ genes affected by PEITC in pancreatic cancer cells were due to induction of ROS and ROS-dependent down-regulation of Sp1, Sp3, Sp4, and pro-oncogenic Sp-regulated genes (30). These results complement studies showing that hydrogen peroxide and t-butylhydroperoxide also down-regulate Sp proteins (22,23,27).BITC is structurally related to PEITC, and both compounds exhibit comparable anticancer activities and modulate expression of some common genes/pathways consistent with their effects on cancer cells (6 -14). It was also reported that BITC inhibits signal transducer and activator of transcription 3 (STAT3) phosphorylation and down-regulates STAT3 protein (6), and another study by the same group showed that BITC also induces ROS in pancreatic and other cancer cell lines (31-33).…”
supporting
confidence: 75%
“…Moreover, knockdown of Sp1 in pancreatic cancer cells decreases growth and invasion and induces apoptosis, confirming the pro-oncogenic functions of this factor (49). These results suggest that drugs such as metformin and other agents (31)(32)(33)(34)(35)(36)39) that target Sp1, Sp3, and Sp4 represent a class of new mechanism-based drugs that can be used in combination therapies for treating this deadly disease.…”
Section: Discussionmentioning
confidence: 62%
“…This involved down-regulation of specificity protein (Sp) transcription factors Sp1, Sp3, and Sp4 and pro-oncogenic Sp-regulated genes such as bcl2, fatty acid synthase (FAS), survivin, vascular endothelial growth factor (VEGF), and VEGF receptor 1 (VEGFR1) (31). The anticancer activities of metformin are also similar to * This work was supported, in whole or in part, by National Institutes of Health that observed after knockdown of Sp1 or all three Sp proteins by RNA interference in cancer cells, and this includes growth inhibition, induction of apoptosis, reversal of epithelial to mesenchymal transition, and decreased migration/invasion (32)(33)(34)(35)(36). Metformin also inhibits NFB and decreases cyclin D1 and ErbB2 in cancer cell lines (13,20,27,28), and these gene products are also decreased after Sp1, Sp3, and Sp4 silencing by RNAi or by other drugs that down-regulate Sp proteins (32)(33)(34)(35)(36).…”
mentioning
confidence: 84%
“…In another study where transgenic LSL-Kras(G12D/+); LSL-Trp53(R127H/+); Pdx-1-Cre (KPC) mouse model of pancreatic cancer were fed with diet containing CDDO-Me or CDDO-ethyl amide, the rexinoid LG100268 significantly increased the survival of mice by 3-4 weeks [209] and prevented lung cancer development when fed with these terpenoids for 8 weeks [15]. CDDO and CDDO-Me fed for 20 week inhibited the progression of the preneoplastic lesions (low-grade PIN and high-grade-PIN) to adenocarcinoma in the dorsolateral prostate (DLP) and ventral prostate (VP) lobes of TRAMP mice [210,211] prevented breast cancer development in BRCA1-mutated mice [212]; pretreatment with oral CDDO-Me improved survival following lethal-dose LPS challenge in mice by modulating the in vivo immune response to LPS [213]; CDDO-Me inhibited orthotopic pancreatic human L3.6pL tumor growth and down-regulated Sp1, Sp3, and Sp4 in tumors [214]. However, these synthetic terpenoids had very poor oral absorption and low bioavailability.…”
Section: Synthetic Triterpenoidsmentioning
confidence: 99%
“…However, these synthetic terpenoids had very poor oral absorption and low bioavailability. To improve its pharmacokinetic profile, a novel CDDO anhydride was synthesized with the same potency as CDDO-Me, but with greater bioavailability [214]. Angiogenesis, particularly 'inflammatory angiogenesis', is a common target of many chemopreventive molecules, which most likely suppress angiogenesis in pre-malignant tumors.…”
Section: Synthetic Triterpenoidsmentioning
confidence: 99%